Immunology of Aging - Massoud, Ahmad; Rezaei, Nima (Springer Berlin Heidelberg : Imprint: Springer, 2014)
The rapidity of scientific progress over the last few years guarantees the utility of a new collection of state-of-the-art reviews on the immunology of ageing. The aim of this authoritative book is to summarize current knowledge on the cellular and molecular aspects of the ageing immune system and their clinical relevance. The book is a result of extensive collaboration of more than sixty of the greatest thinkers and scholars in the field, in cooperation with a number of junior colleagues.   Immunology of Aging presents the most up-to-date information on the scientific issues addressed by research into ageing of the immune system, providing insights into the effects of this process on susceptibilities to those diseases which are most common among elders. The retrieval strategies used to slow down the decline in the immune system in the elderly are another subject detailed extensively.   By providing a broad overview of immunosenescence and its consequences, as well as their potential modulation, this book will fill a gap in a timely manner. It will be of value to all immunologists, whether novice or experienced, as well as geriatricians and epidemiologists.